KAJIAN SOSIAL EKONOMI PEMANFAATAN RICE TRANSPLANTER PADA TANAMAN PADI DI KABUPATEN SIDENRENG RAPPANG - Nispar, Muhammad (Program Studi Agroteknologi, Fakultas Sains dan Teknologi, Universitas Muhammadiyah Siddenreng Rappang, 2022)
In Sidenreng Rappang Regency the use of agricultural technology is one of the choices for farmers to carry out agricultural activities, one example is the combine machine, while the rice planter machine (Transplanter) is still not widely used, because the application of technology in the agricultural sector is also not something easy, because farmers' habits and understanding of technology are still lacking, besides that agricultural activities are also a source of farmers' livelihoods so that farmers do not easily change old habits. The purpose of this study was to determine the use of transplanters, to see the socio-economic influence of farmers on the use of transplanters and to compare the income of farmers in Sidenreng Rappang Regency. The method used in this study is a qualitative and quantitative method using descriptive analysis, income analysis and multiple linear regression analysis. This research was conducted in Watang Sidenreng District, Sidenreng Rappang Regency from April to July 2022. The sampling technique was carried out by simple random sampling and the number of samples selected was 22 farmers. The results of this study indicate that the use of the Transplanter machine at the research location shows that most have implemented the Rice Transplanter rice planting machine. Comparison of the income of the respondent farmers in the application of the transplanter with the manual planting system, it was found that the application of the transplanter machine was more profitable in terms of production costs so that the income was greater due to the reduced total cost. Based on the results of the t test, it can be seen that among the socio-economic factors of rice farmers measured to see their effect on the use of transplanters, it can be seen that the socio-economic factors that are included in the significant category are the factors of the role of farmer organizations with a high level of significance.